Monetary policy committee size and inflation volatility - Szilárd Erhart; Harmen Lehment; Jose Luis Vasquez-Paz (Kiel Institute for the World Economy (IfW), 2007)
Previous research on the optimal size of a monetary policy committee (MPC) focused on theoretical analyses and experimental studies. These studies suggest that the ideal monetary policy committee may not have many more than five members. In this paper we conduct an empirical cross-country study to explore whether there is a link between the size of an MPC and inflation volatility. The analysis for 75 countries which have adopted MPCs provides some support for the above suggestion: countries with less than five MPC members tend to have larger deviations from trend inflation than MPCs with five members; raising the number of MPC members above five does not contribute to a further reduction in volatility.
Keywords: E31; E42; E58; 330; Inflation Volatility; Monetary Policy Committee; Zentralbank; Führungsorganisation; Inflation; Volatilität; Welt